Robust Control of a 2-DOF parallel mechanism combining feedback linearization and H-infinity design. - Stevani, Isabella (2020)
This work presents the robust control of a nonlinear plant with uncertain parameters, in this case a 2-DOF parallel mechanism. First, the robot dynamic and kinematic models were computed using a new methodology based on the serial subsystems models that compose the parallel topology, which are later pieced together through mechanical constraints to form the complete parallel robot model. Then, a robust control architecture combining H? design and feedback linearization was designed in order to guarantee robust performance and stability even in the presence of uncertain parameters in the model. To validate both mechanism\'s modeling and control, simulation results were provided.